Comparison of emergency cesarean hysterectomy with and without prophylactic placement of intravascular balloon catheters in patients with placenta accreta spectrum. (18th August 2022) - Mei, Youwen; Luo, Dan; Wei, Sumei; Wang, Liming; Liao, Xiaoyan; Jing, Huaibo; Lin, Yonghong; Zhao, Hu
Abstract: Objective: The objective of the study was to compare outcomes of women with placenta accreta spectrum(PAS) who underwent emergency cesarean hysterectomy with and without prophylactic intravascular balloon catheters. Methods Sixty-three cases who had emergency hysterectomy related to PAS disorders were retrospectively analyzed. Subjects with prophylactic intravascular balloon catheter placement plus hysterectomy were compared with those who had hysterectomy alone. The cases were divided into three groups: infrarenal aortic artery balloon occlusion (IAABC) group (who had IAABC plus hysterectomy, n = 31), internal iliac artery balloon occlusion (IIABOC) group (who had IIABOC plus hysterectomy, n = 17), and hysterectomy alone group (control group n = 15). Results: Outcome measures were not significantly different between the IIABOC group and the control group. IAABC plus hysterectomy resulted in a better outcome than hysterectomy alone, with less amount of estimated blood loss (EBL) during cesarean section (2000 vs 3000 ml, p = .011) and 24 h after cesarean section (2010 vs 4520 ml, p = .004), less operation time(90 vs 106 min, p = .01), and a lower rate of major blood loss(42 vs 93%, p = .029). IAABC plus hysterectomy resulted in better outcomes than IIABOC plus hysterectomy, with less amount of EBL during cesarean section (2000 vs 3000 ml, p = .005) and 24 h after cesarean section (2010 vs 3000 ml, p = .035), a lower rate of major blood loss(42 vs 100%, p < .001), less operation time (90 vs 100 min, p = .038), and less fetus radiation dose（1.9 mGy vs 22.4 mGy, p < .001). Conclusions: IAABC was more effective in emergency cesarean hysterectomy related to PAS disorders.